The Regencies and Municipalities Population Food Availability and Affordability in Eastern Priangan - Zulfikar Noormansyah; Ivan Chofyan; Faqihuddin Faqihuddin; Dedi Djuliansah (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
The realization of national food security is expected to be built on regional food security. Local governments are obliged to build their own regional food security, and contribute to national security. This is in line with the mandate of Law No. 23/2014 on Regional Government, which states that food is a mandatory matter for the central and regional governments. In relation to this background, this study aims to determine the availability and affordability of food in the East Priangan region, as one of the food production centers of West Java Province. The research method used is mixed method research with the dominance of quantitative design. Based on the results of the analysis, the research can be concluded that the food security conditions of regencies and municipalities in the East Priangan region are categorized as strong. However, based on the results of the comparative analysis among the regencies and cities, it shows a quite unique condition. The condition of the level of food availability (independent) is inversely proportional to the condition of the level of affordability. Regencies and municipalities that have a high marketable surplus of food tend to have a relatively low level of affordability. Conversely, regencies and municipalities with high food affordability have low marketable surplus.